Extraction, characterization, prospecting by GC-MS and bactericide effect of NEEM essential oil (Azadirachta indica) (Research, Society and Development, 2021)
In recent years, there has been an incentive to study essential oils, since these contain insecticidal, antifungal and antibacterial substances in their composition. In this context, Azadirachta indica, popularly known as Neem, due to its biocompounds, has become of great interest in the scientific development community, given that the active ingredients of the plant have antimicrobial and antifungal properties. Therefore, the essential oil was extracted from Neem leaves collected in the Petrolina-PE region, through the technique of ultrasound and extraction by infusion using ethanol and hexane. The antimicrobial activity of Neem oil against Escherichia coli and Staphylococcus spp. by the diffusion technique of discs and mesophilic microorganisms on the surface by the Pour Plate with PCA (Plate Count Agar) and Spread Plate with PDA (Potato Dextrose Agar) techniques, as well as the moisture content of Neem leaves through a greenhouse drying. Inhibition halos of up to 1.1 cm were observed in Escherichia coli, while in Staphylococcus spp. the greatest inhibition was 8 mm. In the inhibition of mesophilic microorganisms there was a drastic decrease in the contamination of the analyzed surfaces, where the oils extracted by both techniques showed great efficiency and promising potential to be used as a control method. Neem leaves had a moisture content of 62.32%. With regard to oil yield, the infusion extraction technique was the most advantageous, but in terms of process time, simplicity and low temperature, the ultrasound technique proved to be superior.